Improving Student Learning Outcomes Through Story Card Media to Find The Main Idea of a Paragraph in Class VI SDN Luwunggede 04 - Kirno, Kirno (Universitas Sebelas Maret, 2020)
The purpose of this study is to improve student learning outcomes in Indonesian lessons in elementary school grade VI by using story cards to find the main idea of a paragraph. The research conducted was Classroom Action Research (CAR) in two cycles, with each cycle having one meeting. The stages of each cycle are the stages of planning, implementation, observation and reflection. Data collection techniques are observation and tests. Based on data analysis, it was found that the use of story card media to find the main idea of paragraphs in Indonesian language lessons to determine the main idea can improve student learning outcomes as indicated by the level of mastery learning in the initial conditions of 40% to 65% in the first cycle, and increased to 80% in cycle II. The final conclusion from the implementation of this classroom action research is that the use of story card media to find the main idea of a paragraph is able to improve student learning outcomes in Indonesian language lessons to determine the main idea at SD Negeri Luwunggede 04, Larangan, Brebes.